POTENSI PEMANFAATAN HASIL HUTAN BUKAN KAYU POHON AREN DI KELURAHAN KAYAWU KOTA TOMOHON - Cindy Eva Saragih; Marthen Theo Lasut; Euis F. S. Pangemanan (COCOS, 2020)
ABSTRACT POTENTIAL UTILIZATION OF NON-AREN FOREST PRODUCTS IN KAYAWU VILLAGE, TOMOHON CITY Sugar palm is one of the HHBK that is widely used, one of which is palm sugar, or also known as "saguer" in the Manado language. Almost all parts of the palm tree can be used. There are many production products that can be used, for example young palm fruit is processed into fro, sap water for making brown sugar and vinegar and starch / flour in the stems for making various foods. This study aims to determine the potential of the sugar palm (Arenga pinnata, Merr.) as a non-timber forest product as utilized by villagers of Kayawu. The research was conducted in November 2019 in Kayawu Village, Tomohon City, North Sulawesi. This research used a purposive sampling method, which is the technique of selecting respondents that fulfill certain criteria and interviewing them using a questionnaire. The results of the study, it can be concluded that the use or processing of palm sugar in Kayawu Village is rock sugar (74.41%), then rat stamp (20.93%) and sugar ant (4.65%). Keywords : HHBK, Palm Sugar, Brown Sugar